2013
DOI: 10.1128/jb.02252-12
|View full text |Cite
|
Sign up to set email alerts
|

The Interacting Cra and KdpE Regulators Are Involved in the Expression of Multiple Virulence Factors in Enterohemorrhagic Escherichia coli

Abstract: The human pathogen enterohemorrhagic Escherichia coli (EHEC) O157:H7 codes for two interacting DNA binding proteins, Cra and KdpE, that coregulate expression of the locus of enterocyte effacement (LEE) genes in a metabolite-dependent manner. Cra is a transcription factor that uses fluctuations in the concentration of carbon metabolism intermediates to positively regulate virulence of EHEC. KdpE is a response regulator that activates the transcription of homeostasis genes in response to salt-induced osmolarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 66 publications
0
35
1
Order By: Relevance
“…However, we also reported that in the presence of E. coli MG1655, E. coli EDL933 switches, at least in part, to gluconeogenesis in order to maintain itself in the intestine, while E. coli MG1655 continues to use glycolytic nutrients exclusively (15). These findings are of extreme interest in view of recent reports showing that E. coli 86-24, also an O157:H7 strain, activates the expression of virulence genes under gluconeogenic conditions (16,17), because this suggests the possibility that precolonization of the intestine with a probiotic E. coli strain that starves E. coli O157:H7 strains of gluconeogenic nutrients might render them nonpathogenic.…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…However, we also reported that in the presence of E. coli MG1655, E. coli EDL933 switches, at least in part, to gluconeogenesis in order to maintain itself in the intestine, while E. coli MG1655 continues to use glycolytic nutrients exclusively (15). These findings are of extreme interest in view of recent reports showing that E. coli 86-24, also an O157:H7 strain, activates the expression of virulence genes under gluconeogenic conditions (16,17), because this suggests the possibility that precolonization of the intestine with a probiotic E. coli strain that starves E. coli O157:H7 strains of gluconeogenic nutrients might render them nonpathogenic.…”
contrasting
confidence: 38%
“…It was reported recently that E. coli 86-24, an O157:H7 strain, activates the expression of virulence genes under gluconeogenic conditions (16,17). The present study was undertaken to determine whether E. coli Nissle 1917, routinely used as a probiotic agent, depletes gluconeogenic nutrients by using them for growth in the mouse intestine, thereby preventing E. coli EDL933, also an O157:H7 strain, from activating virulence gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ethanolamine, a cell membrane component, stimulates ler production through EutR and QseC (38). Gluconeogenic conditions of the large intestine activate the ler activators KdpE and Cra, and butyrate directly activates LEE transcriptional activity (37,125). The RNA chaperone Hfq affects LEE expression through interactions with Ler mRNA but has negative or positive effects depending on the strain of EHEC, as indicated by a dashed arrow (71)(72)(73).…”
Section: Figure 4 Stimulation Of Lee and Non-lee Effector Molecules Rmentioning
confidence: 99%
“…The genes espFu and espJ are influenced by changes in temperature, pH, osmolarity, and oxygen pressure (124). The regulators KdpE and Cra act to increase expression of espFu (125). The QseEF two-component, quorumsensing system controls expression of EspFu through AI-3, epinephrine, and norepinephrine signaling (85) (Fig.…”
Section: Injection Of Effectorsmentioning
confidence: 99%
“…Simi-larly, GI genes can be regulated by proteins encoded by the same GI, another GI, or the bacterial host genome, indicating that GIs are well adapted to their hosts. Therefore, GI genes can be regulated by some environmental signals, such as pH (115), osmolarity (116), temperature (117), cell density (118), or the concentration of specific elements (116,(119)(120)(121).…”
Section: Mobile Elementsmentioning
confidence: 99%